2020
DOI: 10.1016/j.crfs.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between color and antioxidant capacity of fruits and vegetables

Abstract: Visual perception plays a key role in the selection of nutritious and healthy foods. Color, as one of the most important senses of vision, can be used as an indicator of food quality/defects and grade. It is recommended consumers include various colors in their plate to obtain various vitamins and minerals. Color is also thought to be related to antioxidant capacity. Within this regard, this study investigated the relationship between color and antioxidant capacity in various fruits and vegetables. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(101 citation statements)
references
References 35 publications
3
91
0
7
Order By: Relevance
“…Increased concentrations of the phenolic compounds significantly affected the headspace concentration of most aroma compounds, and each polyphenol had a unique effect when combined with a specific aroma compound, either, suppressing, accentuating, or showing little effect on the perception of the aroma compounds. Previous studies have reported the relationship between polyphenolic compounds and color (Comert et al., 2020; Zeb, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Increased concentrations of the phenolic compounds significantly affected the headspace concentration of most aroma compounds, and each polyphenol had a unique effect when combined with a specific aroma compound, either, suppressing, accentuating, or showing little effect on the perception of the aroma compounds. Previous studies have reported the relationship between polyphenolic compounds and color (Comert et al., 2020; Zeb, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate antibacterial activity in this study, heather extracts were prepared using 60% water solution of methanol. In the current study, aqueous ethanol solution was used for detecting the content of some groups of phenolic compounds and antioxidant activity, while aqueous methanol solution was used for indicating antibacterial activity based on the literature [48,49] proving that both solutions appear to be good solvents for phenolic compounds, alkaloids, and saponins that are able to perform antibacterial activity. However, the available published data on the effect of phenolic compounds on gram-negative bacteria turn out to be rather contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that some compounds, including anthocyanins and lycopene, can give similar color to raw materials, but they differ significantly in antioxidant capacity. The relationship between color and antioxidant content should not be generalized to all raw materials, but it can be stated that differences in color usually mean different content of bioactive compounds [23].…”
Section: Discussionmentioning
confidence: 99%